Effect of Sn-xCu Solder Alloy onto Intermetallic Formation After Laser Soldering - Muhammad Asyraf, Abdullah; Siti Rabiatull Aisha, Idris (Springer Nature, 2023)
The awareness of lead-free solders can be attributed to their environmental and human-health related benefits. Due to this consciousness, research toward lead-free solder alloy became a concern. Tin-copper (SnCu) solder alloy is one of the candidates that can meet the characteristic of tin–lead (SnPb). The objective of this study is to analyse the wetting behaviour, intermetallic compound (IMC) thickness and also the spread ratio by varies the copper weight percentage (Cu wt%) in SnCu solder alloy. Solder alloy used was Sn-xCu, where x = 0.0, 0.3, 0.5, 0.7, 1.0 which was soldered onto electroless nickel immersion gold (ENIG) substrate using carbon dioxide (CO2) laser. Parameters used for laser soldering was 35 W for the laser power, focal length was kept constant, scanning time was 0.04 s, and scanning speed was 100 mm/s. Then these sample were subjected to isothermal aging with the duration of 0, 200, 500, 1000 and 2000 h. In the final analysis, the IMC thickness and wetting behaviour characteristics were characterized by metallographic microscopy. The results showed that the higher the Cu percentage in the solder alloy, the higher the thickness formed at the solder joint interface. Besides that, the morphology of IMCs additionally changed with aging time whereby it changed into much uniform and continuous shape, Nonetheless, its thickness was found to be increasing upon aging duration. Furthermore, the spread factor and spread ratio increase, but the equilibrium contact angle decreases with increasing Cu content. These results were the proof that Sn-0.7Cu/ENIG offers a good solder joint performance as compared to other copper percentage.